EFEKTIVITAS PENEGAKAN HUKUM UNDANG-UNDANG TINDAK PIDANA KORUPSI DALAM MENCEGAH TINDAK PIDANA KORUPSI PADA PENGADAAN BARANG DAN JASA PEMERINTAH DI BIDANG KESEHATAN - Iswanti Iswanti; Jafar Sidik; Dudu Duswara Machmudin (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2019)
Health development is essentially an effort carried out by all components of the Indonesian nation that aims to increase awareness, willingness, and ability to live healthy for everyone in order to realize the highest degree of public health, as an investment for the development of socially productive human resources and economical. Once the importance of health services for the community, so that it is included as one of the basic human rights. Apart from being a basic human right, good health services are an indicator of the progress of a nation, because there is a link between the progress of a nation and the health status. In the 2015-2025 Long Term Development Plan, as stipulated in Law Number 17 of 2007, the health sector is included as one of the long-term development directions to realize a competitive nation by building quality human resources, one of which is health development.